Comparative Empathy Levels Among Medical Students at Isfahan University of Medical Sciences - Nasrollah Noori Koohani; Narges Motamedi; Neda Yavari (Health, Spirituality and Medical Ethics)
Background and Objectives: Empathizing, defined as understanding and accepting the feelings, needs, and sufferings of others, is one of the most important components of therapy. The treatment team is responsible for understanding the feelings and worries of the patient. Based on the evaluation of different patients in different conditions, it has been proven that empathy enhances the quality of the mutual relationship between physicians and patients. Methods: The assessment of the relationship between empathy and its related variables has been the subject of various studies over the last decades. The purpose of this cross-sectional study was to evaluate the degree of empathy among medical students of Isfahan University of Medical Sciences. For this purpose, we used the medical student version of the Jefferson scale of empathy (JSE). Results: The empathy among medical students of Isfahan University of Medical Sciences was higher than the mean score on JSE. Medical students’ empathy had no significant relationship with their educational level and gender. Conclusion: There was no significant difference in the level of empathy among the students participating in the research based on gender. There was also no significant difference in the level of empathy toward patients among medical students in basic sciences, clerkship, and internship.